Implementasi Desain Web Interaktif Berbasis Webflow pada UMKM Catering Uni Dina sebagai Strategi Digital Marketing - Agsel Anugrah Budiman; Rafi Ramadino; Sularno Sularno; Zulfitri Yani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study discusses the implementation of an interactive web design based on Webflow for the MSME Catering Uni Dina as an effort to enhance promotion and expand digital marketing reach. In the midst of today’s technological advancements, MSMEs need to utilize digital media to introduce their products and build communication with customers. Through an interactive design approach, the website not only serves as an information medium but also attracts users’ attention and simplifies the ordering process. The design process was carried out through several stages: needs analysis, interface design, and implementation using the Webflow platform. The results show that a responsive and visually appealing website design can increase customer interest and strengthen the business image. Moreover, the use of Webflow has proven to help business owners manage their websites easily without needing to understand programming languages. Therefore, implementing a Webflow-based web design can be an effective digital marketing strategy for MSMEs such as Catering Uni Dina.